2017
DOI: 10.21608/pssjn.2017.33086
|View full text |Cite
|
Sign up to set email alerts
|

Patterns used by Schizophrenic Patients to Cope with Auditory Hallucination

Abstract: Background: Many patients with psychotic disorders experience persistent auditory hallucinations despite rigorous pharmacological treatment. Aim: This study was to assess patterns used by schizophrenic patients to cope with auditory hallucination Methods: Analytical descriptive research design was utilized for the current study.The study was carried out at National Centered for Mental Health-Fhais Hospital-Jordan. Which affiliated to the Ministry of Health at Jordan Governorate. A convenient sample of 55 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Figure (1) demonstrates that 80% of the study group and 55% of the control group were single . Table (2) shows that comparing PANSS positive scores of the study group revealed that there were statistically significant differences between the pre and post intervention. This includes delusions, hallucinatory behavior, grandiosity and suspiciousness (t= 2.764 at p=, 0.014, t=2.400 at p= 0.029, t=5.101 at p= 0.000 & t = -2.496 at p= 0.024) respectively.…”
Section: Figure 1frequency Distribution Of Marital Status Of the Study And The Control Group (N=20)mentioning
confidence: 96%
See 1 more Smart Citation
“…Figure (1) demonstrates that 80% of the study group and 55% of the control group were single . Table (2) shows that comparing PANSS positive scores of the study group revealed that there were statistically significant differences between the pre and post intervention. This includes delusions, hallucinatory behavior, grandiosity and suspiciousness (t= 2.764 at p=, 0.014, t=2.400 at p= 0.029, t=5.101 at p= 0.000 & t = -2.496 at p= 0.024) respectively.…”
Section: Figure 1frequency Distribution Of Marital Status Of the Study And The Control Group (N=20)mentioning
confidence: 96%
“…Figure(2) illustrates that half of the sample of the study group were highly educated and 45% of the control group were intermediately educated. While 15% & 20% of the study and the control groups could read and writePart 2: Comparison between pre and post HIP among study group regarding the scores of PANSS positive scale…”
mentioning
confidence: 99%